2022
DOI: 10.1200/jco.2022.40.16_suppl.3122
|View full text |Cite
|
Sign up to set email alerts
|

Results of a phase II trial of the PARP inhibitor, niraparib, in BAP1 and other DNA damage response pathway deficient neoplasms.

Abstract: 3122 Background: BRCA1-Associated Protein 1 (BAP1) acts as a tumor suppressor and critical regulator of the cell cycle and DNA damage response (DDR). PARP inhibitors (PARPi) demonstrate synthetic lethality in BAP1 mutant (mBAP1) preclinical models, independent of underlying germline BRCA status. mBAP1 leads to a loss of functional protein in several solid tumors. This study aimed to explore the clinical activity of niraparib in patients (pts) with advanced tumors likely to harbor mBAP1. Methods: Eligible adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…BAP1 appears one such biomarker gene which is mutated in a large fraction of mesothelioma and has been used for exploring pharmacologically targetable vulnerabilities for patients lacking BAP1. For instance, a recent study assessed the clinical activity of PARP inhibition using niraparib in patients with advanced tumors likely to harbor mutated BAP1 ( 33 ). While clinical benefit was identified in the majority of patients with a mutated BAP1 tumor, the use of niraparib failed to meet the prespecified efficacy threshold of an objective response rate.…”
Section: Discussionmentioning
confidence: 99%
“…BAP1 appears one such biomarker gene which is mutated in a large fraction of mesothelioma and has been used for exploring pharmacologically targetable vulnerabilities for patients lacking BAP1. For instance, a recent study assessed the clinical activity of PARP inhibition using niraparib in patients with advanced tumors likely to harbor mutated BAP1 ( 33 ). While clinical benefit was identified in the majority of patients with a mutated BAP1 tumor, the use of niraparib failed to meet the prespecified efficacy threshold of an objective response rate.…”
Section: Discussionmentioning
confidence: 99%
“…A phase two clinical trial of the PARPi rucaparib in BAP1-deficient or BRCA1-deficient MM showed disease control rate of 58% at 12 weeks 23. Another ongoing phase two clinical trial using the PARPi niraparib led to partial response or stable disease in 78% of patients with refractory metastatic tumours and BAP1 mutations 24…”
Section: Discussionmentioning
confidence: 99%
“…Since deleterious mutations in SWI/SNF or BAP1 detected in > 30% of this 128-patient cohort are potentially actionable [ 5 , 7 , 8 ], it is crucial to reliably identify them. Still, the pathogenicity of SWI/SNF genes alterations remains vastly unknown.…”
Section: Epigenomic Alterationsmentioning
confidence: 99%